Effect of receiving a customizable brochure on breast cancer patients' knowledge about their diagnosis and treatment: A randomized clinical trial - Villarreal-Garza, C (2023)
Background: Patients' lack of knowledge about their own disease may function as a barrier to shared decision-making and well-being. This study aimed to evaluate the impact of written educational materials on breast cancer patients. Methods: This multicenter, parallel, unblinded, randomized trial included Latin American women aged ≥18 years with a recent breast cancer diagnosis yet to start systemic therapy. Participants underwent randomization in a 1:1 ratio to receive a customizable or standard educational brochure. The primary objective was accurate identification of molecular subtype. Secondary objectives included identification of clinical stage, treatment options, participation in decision-making, perceived quality of information received, and illness uncertainty. Follow-up occurred at 7–21 and 30–51 days post-randomization. ClinicalTrials.gov identifier: NCT05798312. Results: One hundred sixty-five breast cancer patients with a median age of 53 years and 61 days from diagnosis were included (customizable: 82; standard: 83). At first available assessment, 52%, 48%, and 30% identified their molecular subtype, disease stage, and guideline-endorsed systemic treatment strategy, respectively. Accurate molecular subtype and stage identification were similar between groups. Per multivariate analysis, customizable brochure recipients were more likely to identify their guideline-recommended treatment modalities (OR: 4.20,p = 0.001). There were no differences between groups in the perceived quality of information received or illness uncertainty. Customizable brochure recipients reported increased participation in decision-making (p = 0.042). Conclusions: Over one third of recently diagnosed breast cancer patients are incognizant of their disease characteristics and treatment options. This study demonstrates a need to improve patient education and shows that customizable educational materials increase patients' understanding of recommended systemic therapies according to individual breast cancer characteristics.